Molecular detection of two new putative species of gammaherpesvirus in petaurid possums. Issue 11 (30th August 2022) - Douch, JK; Devlin, JM; Whiteley, P; Hartley, CA; Vaz, PK
Abstract : A molecular survey of herpesviruses in Australian native mammals was conducted, spanning 260 individuals from 27 species. Among the herpesviruses detected, a putative new gammaherpesvirus species was detected in the yellow‐bellied glider ( Petaurus australis ), and another in the critically endangered Leadbeater's possum ( Gymnobelideus leadbeateri ). In addition, the known host range of the putative species macropodid gammaherpesvirus 3 (MaHV‐3) is herein extended to the western grey kangaroo ( Macropus fuliginosus ). These findings expand our understanding of herpesviruses in Australian mammals and may inform biosecurity protocols for captive and translocated populations.